ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERHITUNGAN PPH BADAN PADA PERUSAHAAN PEMBIAYAAN DI PT. HASJRAT MULTIFINANCE MANADO - Rantung, Allbrian J. W.; Saerang, David P. E.; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
One of the largest sources of state revenue in the tax sector is bandan income tax / PPh 29. This study aims to determine what factors influence the calculation of corporate income tax on finance companies at PT. Hasjrat Multifinance Manado. This research uses descriptive method which is used to find out how many factors influence the calculation of corporate income tax.From the results of the study it is known that there are several factors that influence the calculation of corporate income tax, namely the factor of sales contribution on credit by the dealer, the interest rate factor and the administrative revenue factor. The results of this study indicate that these factors are the main source of income for finance companies, thus affecting the calculation of Corporate Income Tax. The greater the contribution of the dealer will affect the value of financing, and the value of financing will affect the value of revenue and revenue of the company so that automatically the greater the contribution of corporate income tax/PPh 29. Keywords :Financing contributions, installments and interest income, taxes